Analisis Penerapan Sistem Manajemen Mutu pada McDonald’s TB Simatupang - Muhammad Thria Wardhani; Hamzah Rabbani; Hapsari Widayani (FOCUS, 2022)
This study aims to analyze the application of a quality management system at McDonalds TB Simatupamg. The type of research carried out was a qualitative case study. Data collection techniques using interviews, observations. The data analysis techniques were collecting data, organizing data, reading and making memos, describing cases and their contexts, clarifying data into code and themes using aggregation, interpreting data, presenting and visualizing data. The results of the study showed that the point of the clause focused on the customer well but had a record of the point of customer requirements and the rules and regulations were determined and met sometimes still sometimes not met but the company made customer recovery so that it was met..